GERAKAN BIJAK REM NIKAH (GEBRAK) BAGI REMAJA DESA KRAMAT SUKOHARJO DAN SISWA SMPN 6 TANGGUL - Risnitasari, Mithaqul; Agustin, Ayu Tri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Early marriage is defined as an anomaly that continues to occur and is increasingly widespread, Lack of understanding about young marriage makes children experience deep wounds. (Darmawan, 2021). The implementation of GEBRAK (wise marriage brake movement) was carried out in two places. The first place is in the village hall and the second is at SMPN 6 Tanggul. This research is qualitative research. From the results presented, several steps to overcome early marriage have been taken not only from the KUA and village officials but also several students who are having duty obligations in this Kramat village. Forms of Student Implementation to Overcome Early Marriage We are required to provide solutions to reduce various existing problems. Someday the knowledge taught when in someone else's village can be brought, moreover it can be implemented into the village of his birth. Based on the survey results, it was found that early marriage is caused by internal & external factors. Through discussions in the â€œGEBRAKâ€ socialization, it is hoped that it can reduce the number of early marriages in Jember Regency, especially in Kramat Sukoharjo Village.